2019
DOI: 10.1111/ijd.14692
|View full text |Cite
|
Sign up to set email alerts
|

Update on treatments for erosive vulvovaginal lichen planus

Abstract: Vulvovaginal lichen planus (VVLP) is a debilitating disease that causes significant pain and psychological distress. Management is made difficult by the chronic course of the disease and its resistance to treatment. While topical steroids have been accepted as the first-line treatment, they fail to achieve symptomatic control in approximately 40% of patients.Second-line therapies include other topical treatments such as calcineurin inhibitors, systemic therapies including oral steroids, methotrexate, mycopheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(69 citation statements)
references
References 35 publications
0
67
0
Order By: Relevance
“…Previous research has shown that ELPV is a difficult to treat condition. 2,3 This study suggests that HCQ can be an effective treatment in ELPV. Overall, 60% of the patients responded to HCQ, with almost half experiencing a longterm effect.…”
mentioning
confidence: 72%
See 4 more Smart Citations
“…Previous research has shown that ELPV is a difficult to treat condition. 2,3 This study suggests that HCQ can be an effective treatment in ELPV. Overall, 60% of the patients responded to HCQ, with almost half experiencing a longterm effect.…”
mentioning
confidence: 72%
“…Dear Editor , Erosive lichen planus affecting the vulva and vagina (ELPV) is a rare inflammatory skin disease, presenting with painful erosions and severe scarring 1 . The disease course is persistent and often refractory to treatment: up to 45% of patients do not experience remission with topical treatments, and evidence for systemic treatments remains scarce 2 . Hydroxychloroquine (HCQ) is frequently used in daily practice as a first choice systemic therapy 3 .…”
Section: Treatment Characteristics (N = 15) Valuesmentioning
confidence: 99%
See 3 more Smart Citations